The Antioxidant Capacity of Peristrophe Bivalvis (L.) Merr. as Natural-Based Nephroprotection - Ketut Agus Adrianta; Bagus Komang Satriyasa; Desak Made Wihandani; I Made Jawi (Majalah Obat Tradisional, 2021)
The kidneys as one of the important body organs have a very important role in maintaining a healthy body. The kidneys function to regulate fluid balance in the body the concentration of salt in the blood, acid-base balance in the blood, and excretion of waste materials such as urea and other nitrogenous waste in the blood. Magenta plants (Peristrophe bivalvis (L.) Merr.) contain secondary metabolites, namely alkaloids, saponins, triterpenoids, tannins, and flavonoids as antioxidants. The abundance of antioxidants sourced from natural sources for various diseases is often used as a complementary therapy and is one of the current therapeutic choices. However, the development of natural sources must also consider kidney function during an intervention. The incidence of kidney failure can be caused either by the occurrence of oxidative stress or exposure to drugs and other chemical compounds must also consider the physiological functions of important organs in the body such as the liver and kidneys. This study was conducted to determine the protective role of magenta leaves extract (Peristrophe bivalvis (L.) Merr.) on the kidneys after being given an acetaminophen hepatotoxic dose. In this study, the effectiveness of magenta leaves antioxidants and the safety of use was analyzed by looking at the kidney function in the experimental model of Wistar strain male white rats, using a Randomized Post Test Only Control Group Design. Four treatment groups showed that magenta leaves extract (Peristrophe bivalvis (L.) Merr.) at 125 and 250 mg/kg BW can protect the kidneys with average creatinine levels of 0.63 and 0.75 and with a normal range (0.7 - 1.2). It means that these two groups could protect the kidney function although in the histopathology test only the group administering extracts of 250 mg/Kg BW showed good results. It can be concluded that administration of the magenta leaves extracts at 250 mg/kg BW can protect renal function as seen from serum creatinine levels. Besides, histopathological features can provide a protective effect on the kidneys with the incidence of necrosis in the kidneys of less than 60% of the toxic dose of acetaminophen.